2020
DOI: 10.1590/s0102-865020200010000005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of HSP90 in ischemic postconditioning-induced cardioprotection by inhibition of the complement system, JNK and inflammation

Abstract: Purpose: To investigate whether heat shock protein 90 (HSP90) is involved in complement regulation in ischemic postconditioning (IPC). Methods:The left coronary artery of rats underwent 30 min of occlusion, followed by 120 min of reperfusion and treatment with IPC via 3 cycles of 30s reperfusion and 30s occlusion. The rats were injected intraperitoneally with 1 mg/kg HSP90 inhibitor geldanamycin (GA) after anesthesia. Eighty rats were randomly divided into four groups: sham, ischemia-reperfusion (I/R), IPC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…This was consistent with the findings of Sugiura et al ( 28 ), which showed that in an ischemic acute kidney injury model, klotho inhibited apoptosis via Hsp70. Previously, Hsp90 was found to exert a profound ischemic postconditioning cardioprotective effect and to alleviate I/R-induced myocardial injury and apoptosis in vivo ( 36 ). Notably, the western blotting results of the present study showed that klotho overexpression in H9c2(2-1) cells prior to H/R treatment upregulated the levels of p-Akt and p-Bad.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the findings of Sugiura et al ( 28 ), which showed that in an ischemic acute kidney injury model, klotho inhibited apoptosis via Hsp70. Previously, Hsp90 was found to exert a profound ischemic postconditioning cardioprotective effect and to alleviate I/R-induced myocardial injury and apoptosis in vivo ( 36 ). Notably, the western blotting results of the present study showed that klotho overexpression in H9c2(2-1) cells prior to H/R treatment upregulated the levels of p-Akt and p-Bad.…”
Section: Discussionmentioning
confidence: 99%
“…In unstressed cells, the HSF1 monomer is retained in the cytoplasm in a complex with HSP40, HSP70, and HSP90, as well as the TRiC [ 20 ]. The decrease in HSF1 protein levels may lead to the increase of unbound chaperone proteins including HSP90, which in turn plays roles in suppressing the expression of C3 and inflammatory cytokines, as shown in ischemic postconditioning-induced cardioprotection [ 48 ]. However, the postulation needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Activated by cellular stress, HSP90 plays a central role in myocardial I/R injury and cardioprotection during ischemic preconditioning and pharmacological conditioning [ 5 , 7 , 25 ]. Our laboratory recently found the important role of HSP90 in postconditioning [ 6 , 19 , 26 , 27 ]. HSP90, especially in the mitochondria, facilitates translocation of mitochondria proteins in cardioprotection against I/R-induced injury.…”
Section: Discussionmentioning
confidence: 99%